National Systems of Innovation and Non-OECD Countries: Notes about a rudimentary and tentative “typology” - Albuquerque, Eduardo da Motta e (Brazilian Journal of Political Economy, 1999)
This paper suggests a tentative “typology” for Non-OECD National Systems of Innovation (NSIs). Three main categories compose this tentative “typology”: “mature” NSIs, catching up NSIs, and “non-mature” NSIs. This paper investigates theoretical mediations which may be necessary if the NSI concept is to be applied appropriately to Non-OECD countries. Science and technology statistics are used to evaluate the suggested “typology”. Basic statistics (GDP, R&D expenditures, education, patents, and papers) are presented. Data from forty-six countries are used for statistical exercises. The findings of this paper hint that it is possible to cluster different countries around science and technology indicators. JEL Classification: O33; O35; O43.